(untitled) (MAUSAM, 1990)
An investigation has been made on the behavior of the thermal plume height in the daytime Convective Boundary Layer (CBL) using facsimile record data obtained from a Doppler Sodar which has been ill operation at Thumba, at a site located close to the Arabian Sea coast. The records from 1983 to 1987 have been taken to observe the typical features of the boundary layer at Thumba. To study the daytime variation of the thermal plume height in relation to surface temperature, 140 clear days in the year 1984 have been chosen. Thermal plume heights were found to peak between 1000 & 1200 IST during January to May 1984, with an exception of April, and from October to December 1984. For the rest of the months, it is seen that the daytime variation does not show any significant peak. The results are discussed III detail.